Studi Sistem Pengelolaan PLTS 15 kW Stand Alone Dengan Metode Kano Di Dusun Yeh Mampeh Kabupaten Bangli - Andita Putra, IGA; Giriantari, IAD; Kumara, I NS (Majalah Ilmiah Teknologi Elektro; Vol 14 No 1 (2015): (January - June) Majalah Ilmiah Teknologi ElektroDO - 10.24843/MITE.2015.v14i01p03)
Management of PLTS 15 kW stand alone at Yeh mampeh village, bangli regency implemented for PLTS can be utilized optimally and sustainable. Sistem management referring to the results of PLTS component with life time of that and results of the questionnaire. Questionnaire were taken by using Kano Method with 50respondent. Kano categoryused in this study are one dimensional, attractive, must be, indiferent, reverse. This method produces the desired management system of PLTS customers are workers will work twince in one week to four hours every day working with two workers, each employee is given a saary of Rp.300.000, PLTS depreciation is Rp. 3.896.000, with the expected quantity of PLTS customer 150th , so the contribution of each customer every mount is Rp. 28.000. If this sistem can be running by society of Yeh Mampeh Village, then PLTS will be utilized optimally and sustainable.
Keywords: Metode kano , Life Time, Komponen PLTS, Pelanggan PLTS